Manajemen Konflik dalam Organisasi: Tinjauan Literatur Sistematis tentang Variasi Jenis, Faktor Penyebab, dan Strategi Penanganan (International Forum of Researchers and Lecturers, 2025)
Conflict is an inevitable phenomenon in every organization, whether in business, education, or social contexts. If not managed properly, conflict has the potential to reduce performance; however, if handled constructively, it can become a source of innovation. Based on this issue, this study aims to answer the main question: how is conflict understood and managed according to recent literature findings? The method used is a literature review by searching for articles through several online databases using the keywords